The Century-Old Swinging of Russia Between Order and Dissolution, East and West: A Historical and Psychocultural Insight in the Russian-Ukrainian War - Facco, Enrico; Tagliagambe, Silvano (Advances in Social Sciences Research Journal, 2022)
The aim of this article is to analyze the recent Russian behavior from a historical, cultural and psychological perspective in the attempt to better understand the sudden shift from a western oriented policy to the rejection of the West and the shift toward the East. In the West, progress has been conceived as a process of controlled linear change in the hope to develop and improve prosperity and wellbeing along the arrow of time. On the other hand, any change has been always conceived as an eschatological overturning in Russia, where the previous condition is radically refused and the new one is the result of its turn upside down. On psychological standpoint, this dual structure seems to depend on proneness to splitting and inability to integrate the opposites - a behavior similar to primary defense mechanisms of the infants that may persist in adult life. The Russian psychocultural inclination to a dual axiological structure also is in line with the dualist Orthodox religious belief, contemplating only heaven and hell and denying purgatory. The above century-old dual structure of Russian mentality is also compatible with Putin’s dual behavior, initially reproaching the West and then radically refusing it as a sort of absolute evil.